Changes in Expression and Cellular Localization of Rat Skeletal Muscle ClC-1 Chloride Channel in Relation to Age, Myofiber Phenotype and PKC Modulation - Conte, Elena; Fonzino, Adriano; Cibelli, Antonio; De Benedictis, Vito; Imbrici, Paola; Nicchia, Grazia Paola; Pierno, Sabata; Camerino, Giulia Maria (Frontiers in Pharmacology, 2020)
The ClC-1 chloride channel 1 is fundamental to modulate the correct sarcolemma electrical stability. We investigated the contribution of ClC-1 to adaptation of skeletal muscles to needs induced by the different stages of life. We analyzed the ClC-1 gene and protein expression as well as mRNA levels of protein kinase C (PKC) Alpha and Theta involved in ClC-1 modulation, in soleus (SOL) and extensor digitorum longus (EDL) muscles of rats in all stage of life. Also, we followed the cellular localization of ClC-1 in relation to age. Our data show that ClC-1 expression during muscle development is different according to phenotype. In fast EDL muscles the ClC-1 expression increases by 10-fold starting at 7-days until 8-months of rats life. Differently, in slow SOL muscles the ClC-1 expression remain constant until 33-days of life, and after, it increases by 5-fold to reach the adult value. Aging induces a downregulation of gene and protein ClC-1 in both analyzed muscles. The mRNA of PKC-theta has the same trend of ClC-1 except for the old-age; differently, the PKC-alpha mRNA increases only after 2-months of age. Also, we found that the ClC-1 is localized in both membrane and cytoplasm, in fibers of 12-days old rats, becoming perfectly localized on the membrane in 2-months old rats. The ClC-1 plays a key-role in the induction of correct muscles phenotype development during the muscle growth. This study could represent a point of comparison helpful for the identification of accurate pharmacological strategies for all the pathological situations in which ClC-1 protein is altered.